DOL NET FISHERY OF NAWABUNDER (GUJARAT) - KHAN, MOHAMMAD ZAFAR (Fishery Technology, 2017)
Extimated catch of 6,484.9; 3,505.6 and 4,797.7 t of fishes were landed at Nawabunder in 'dol.' net during 1976-77, 1977-78 and 1978-1979 respectively. There has been an increasing trend. in effort and decline in catch and catch rate. The catch rate came down from 174.8 kg in 1976-77 to 84 kg in 1978-79. The detailed studies on the catch composition revealed that the Bombay duck formed about 68.6 - 77%of the total catch. The other important constituents being Coilia dussumieri 1.5 9.2%, ribbon fish 3.0 - 6.5%, non-penaeid prawn, namely, Acetus indicus, Nematopalaemon tenuipes and Hippolysmata ensirostris together formed about 6.1 - 13.7% and penaeid prawns 1.5- 3.1% of the total `dol' net landings. In addition, quality fishes such as `ghol', 'warn', pomfret and catfishes were also landed in considerable quantities. The landings of `ghol' is on the increase from 4.9 t in 1976-77 to 59 t in 1978-79. Large number of juveniles of economically important fishes namely, Harpodon nehereus,Pampus argenteus, Trichiurus lepturus and Ilisha filigera have been observed in the catch particularly during February-May. The destructive nature of the gear has been commented along with the suggestions for regulation of the fishery.